ВОЗНИКНОВЕНИЕ ДЕФЕКТОВ ПРИ ЭЛЕКТРОННОМ ОБЛУЧЕНИИ СИНТЕТИЧЕСКИХ HPHT-АЛМАЗОВ ПО ДАННЫМ ПОЗИТРОННОЙ АННИГИЛЯЦИОННОЙ СПЕКТРОСКОПИИ (Письма в ЭЧАЯ, 2024)
The concentration of negatively charged vacancies resulting from electron irradiation of a synthetic single-crystal diamond plate with nitrogen-substituted vacancies was calculated. The concentration was calculated using IR spectroscopy and analyzed using PAS positron annihilation spectroscopy. It is shown that PAS and the use of a monochromatic positron beam can be used for non-destructive monitoring of the vacancy concentration along the depth of a diamond plate.